Temperature Effects on Rheological Properties of Fresh Thickened Copper Tailings that Contain Cement - Yong Wang; Aixiang Wu; Zhuen Ruan; Hongjiang Wang; Yiming Wang; Fei Jin (Journal of Chemistry)
Cemented paste backfill (CPB) is an economic and environmental friendly technique applied in underground mining for supporting surrounding rock and replacing the pillar. However, little is known about the temperature effects on CPB in mines having a large temperature fluctuation. The main purpose of this research was to investigate the effect of temperature change on the rheological properties (e.g., shear stress and apparent viscosity) of CPB with copper mine tailings. Specifically, a series of rheological tests were conducted on 6 CPB samples using a Brookfield R/S+ Rheometer under various temperatures (2°C, 10°C, 20°C, 30°C, 40°C, and 60°C). Our results showed that both shear stress and apparent viscosity of these tailing samples increased with temperature rising from 2 to 60°C. Likewise, temperature has a significant impact on the Bingham yield stress of thickened tailings. The yield stress decreased from 122 Pa (2°C) to 112 Pa (20°C) and then increased to 152 Pa (60°C). Moreover, the pipeline transport pressure drop of CPB at various temperatures was calculated, illustrating an obvious effect on the paste pipeline transport. Compared with 20°C, the pressure drop under 2°C and 60°C increased by 11% and 22%, respectively. The results of this study indicate that the temperature plays an essential role in determining rheological properties of CPB and its engineering application in mines particularly with naturally fluctuating temperatures.